Development of an extended topology-based lightweight cryptographic scheme for IEEE 802.15.4 wireless sensor networks - Walter Tiberti; Federica Caruso; Luigi Pomante; Marco Pugliese; Marco Santic; Fortunato Santucci (International Journal of Distributed Sensor Networks)
Among the classes of wireless personal area networks, a wireless sensor network typically refers to a versatile and densely distributed sensing platform that enables the support of a wide variety of application domains. Among the various technical challenges addressed by more than one decade of research in wireless sensor networks, security across wireless links is by far one of the most critical ones and relates to the need of guaranteeing reliability and trustiness of the collected data. This article deals with the cryptographic aspects involved in securing wireless sensor networks, in terms of confidentiality and authentication. In particular, moving from some results previously achieved in our research activity, this article extends a cryptography scheme in order to better comply with the security requirements that arise from real-world wireless sensor network installations. The proposed scheme, called topology-authenticated key scheme 2, takes advantage of hybrid cryptography to provide security in the presence of resource-constrained sensor nodes using topology-authenticated keys to provide increased robustness to the scheme itself. The proposed extensions provide full practical support to star-topology wireless sensor networks and the article presents also some experimental results obtained by implementing the scheme on two different wireless sensor network platforms available for protocol stacks compliant with the IEEE 802.15.4 standard.